Early time course of the acute phase protein response in man. Issue 2 (February 1983) - Colley, C M; Fleck, A; Goode, A W; Muller, B R; Myers, M A
Abstract : The rate at which the acute phase protein response occurred after both major and minor surgery was explored. Increases in the plasma concentration of C-reactive protein (CRP), alpha-1-acid glycoprotein (alpha 1 AG) and fibrinogen were not detected until 6-8 h after the initial incision. The peak concentration of CRP occurred at 48 h and that of fibrinogen at 96 h; alpha 1 AG concentrations rose rapidly until 48 h followed by little change until about 120 h. Although there was widespread variation in the concentrations of individual proteins in patients, severity of injury did not seem to have a significant effect on the time course of the change. Plasma cortisol concentration and the total white blood cell count (WBC) reached their peaks before the acute phase proteins, cortisol at 6 h and WBC at 12 h.